K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

8 tháng 9 2016

a)\(-\frac{5}{13}:\left(\frac{145}{28}-\frac{17}{9}.\frac{5}{4}+\frac{79}{63}\right)\)

    \(=-\frac{5}{13}:\left(\frac{145}{28}-\frac{85}{36}+\frac{79}{63}\right)\)

    \(=-\frac{5}{13}:\left(\frac{145}{28}-\frac{31}{28}\right)\)

    \(=-\frac{5}{13}:\frac{57}{14}\)

   \(=-\frac{70}{741}\)

17 tháng 10 2015

A = \(-\frac{513}{100}:\left(\frac{145}{4.7}-\frac{17}{9}.\frac{5}{4}+\frac{79}{7.9}\right)=-\frac{513}{100}:\frac{145.9-17.5.7+79.4}{4.7.9}=-\frac{513}{100}:\frac{57}{14}\)

A = \(-\frac{513}{100}.\frac{14}{57}=\frac{-63}{50}\)

22 tháng 10 2015

hoang xuan ngan bạn tả lời sai rồi đó nhiên

\(=-5.13:\dfrac{16}{3}=-\dfrac{513}{100}\cdot\dfrac{3}{16}=\dfrac{-1539}{1600}\)